Identities and Insecurities: Selves at Work - Collinson, David L. (Organization (London, England), 2003)
This article explores the growing interest in selves and subjects at work. In particular, it examines the analytical importance of insecurity for understanding the subjective power relations and survival strategies of organization. Insecurity in organizations can take many different, sometimes overlapping forms. Highlighting how these insecurities can intersect in the reproduction of workplace selves and organizational power relations, the article argues that attempts to overcome these insecurities can have contradictory outcomes. It also illustrates how `conformist', `dramaturgical' and `resistant' selves may be reproduced, particularly in surveillance-based organizations. The article concludes that a greater appreciation of subjectivity and its insecurities can enhance our understanding of the ways that organizational power relations are reproduced, rationalized, resisted and sometimes even transformed within the contemporary workplace.